Preserved brain metabolic activity at the age of 96 years. (10th May 2016) - Apostolova, Ivayla; Lange, Catharina; Spies, Lothar; Ritter, Kerstin; Mäurer, Anja; Seybold, Joachim; Fiebach, Jochen B.; Steinhagen-Thiessen, Elisabeth; Buchert, Ralph
Abstract : Loss of brain tissue becomes notable to cerebral magnetic resonance imaging (MRI) at age 30 years, and progresses more rapidly from mid 60s. The incidence of dementia increases exponentially with age, and is all too frequent in the oldest old (≥ 90 years of age), the fastest growing age group in many countries. However, brain pathology and cognitive decline are not inevitable, even at extremely old age (den Dunnen et al., 2008 ).